Epigenetic Regulation of Breast Cancer Stem Cells - Yunita, Elvira (Biomedical Journal of Indonesia, 2021)
Breast cancer arises as a result of abnormal breast cells forming at an uncontrolled rate. Death in this case of breast cancer is due to the ability of cancer cells to adapt so that it can have an effect on metastasis and recurrence of cancer that was previously thought to have been resolved. The results showed, there is a stem cell population in breast cancer cases which will cause breast cancer to become increasingly difficult to treat. Such cells are known as breast cancer stem cells.Breast cancer cells have the ability to differentiate and contribute greatly to the breast cancer program, as well as to resistance to therapy. Therefore, epigeneticregulation of breast cancer cells is important to study in order to overcome cancer so that it can overcome progression and resistance to cancer therapy being carried out.Epigenetic regulation that has been known in cancer cases includes DNA methylation, histone acetylation, histone methylation and epigenetic regulation by miRNA. DNA methylation is the addition of a methyl group to the nitrogen base of DNA cytosine which will force the DNA transcription process. Acetylation of theaddition of an acetyl group at the end of the histone causes reduced chromatin condensation so that it will activate the transcription process. Methylation histones will also suppress transcription so that genes cannot be expressed. In addition, there is also a small RNA molecule known as miRNA which can bind to the transcribed mRNA. This binding will cause the mRNA to degrade or inhibit its translation.